Emotions associated with the process of construction the parallelepiped volume - Vinces-Vinces, Fabricio Vladimir (2022)
This study analyzes the emotions of students between 14 and 17 years of age when they autonomously construct a rectangular box in 2D and 3D that represents the volume of a parallelepiped, using Cabri II Plus software. The methodology was based on frequency analysis using heat maps constructed with the Python computing tool. Using non-probabilistic sampling, and with the prior informed consent of their legal representatives, 34 ninth grade elementary school students were selected from a public educational institution in the city of Medellin, Colombia, of whom 28 participated in this study. Emotion was considered from a comprehensive point of view, taking into account its evolutionary, physiological-neural, cognitive, volitional and expressive aspects. FaceReader software, a specialized tool for detecting facial expressions, was used to capture these emotions. The results showed that, due to difficulties in the construction process, emotions such as sadness, anger, neutrality, fear, disgust and surprise were experienced. In the population studied, a correlation between emotional processing capacity and cognitive processing was detected. It was concluded that, when faced with difficulties in geometric construction that required drawing parallel lines and perpendicular lines, the difference between one point of intersection and another, and the relationship between the area or volume of a parallelepiped in 2D and 3D, negative emotions associated with the lack of mastery of these concepts emerged which, if students cannot exercise self control, can inhibit their cognitive processing, blocking their mental activities and leading them to abandon the task.